Acute diarrhoea in adults. (15th June 2009) - Jones, Roger; Rubin, Greg
Abstract : A common condition provides an example of the use of the test of time in diagnosis, explained in the accompanying article by Susanna Almond and Nick Summerton (doi: 10.1136/bmj.b1878 )